Self-development of Teacher Students through Problem-Based Learning - Titiworada Polyiem; Prasart Nuangchalerm (Journal of Educational Issues, 2024)
World of education is now changing and requires lifelong learning, self-development, and dealing with the sustainable development. The goal of this study is to look into the self-development of teacher students through problem-based learning. The participants were 78 Thai teacher students from a single university. For the study, data were examined using the mean, standard deviation, Pearson’s product moment correlation coefficient, and content analysis. The outcomes of the study revealed that teacher students had a high level of self-development in learning skills in relation to the Qualifications Framework for Higher Education. Cognitive skills, morals and ethics, knowledge, interpersonal connections and responsibility, learning management, numerical analysis, and communication and information technology abilities were the students’ top six skills.